(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2020)
The present essay is an extended conversation between the authors, on the critical literature of the experimental women’s cinema and video and documentaries of Colombian female artists. The meaning of self, womanhood, and female artistic practices is in the focus of the conversation. Methodologically we approach this essay as warmipura, a female circle, or rather, as we propose, maternal space of kin and alliance-making with multiple others around and within us. It is the space of porous openness to the world, the community, co-working and co-knowing, all together the process of co-creating with multiple others both human and non-human. Openness to the other in self while seeing self in the other allows making new alliance, that in their turn open up the new worlds to explore, their potentialities. Experimental practice is seen as such maternal space, an assemblage using Deleuze-Guattarian term, of bits of life, adopting Smelik and Lykke’s words. Largely informed by the feminist new materialism and posthumanism, the essay explores the alliances, intentionally, intuitively, and organically happening in the maternal space of warmipura. The present essay focuses on the vitality of fragments and allies in the process of disassembling self through and with the video practice.